A new fossil caridean shrimp (Crustacea: Decapoda) from the Cretaceous (Albian) of the Romualdo Formation, Araripe Basin, northeastern Brazil - Santana, William Ricardo Amancio [UNESP]; Pinheiro, Allysson Pontes; Silva, Caroline Mayara Rodrigues da; Saraiva, Antônio Álamo (Magnolia Press, 2013)
A new fossil caridean shrimp, Kellnerius jamacaruensis n. gen. n. sp., of the early Cretaceous (Albian) from the Romualdo Formation, Araripe Basin, northeastern Brazil is described and illustrated. The new species is compared to known fossil palaemonids found in Brazil. Kellnerius jamacaruensis n. gen. n. sp. is easily differentiated from the other palaemonids by a rostrum with 5 spines, an enlarged scaphocerite that is longer than the rostrum, and a third somite with a distinct groove in the tergite that does not extend to the pleurite.
Keywords: Fossils concretions; Palaemonidae; Santana group; Crato formation